4-Methyl-2-oxo-2H-chromen-7-yl 4-fluorobenzenesulfonate - Madhukar Hemamalini; Hoong-Kun Fun; Habibah A. Wahab; Hasnah Osman; Suman Sinha (Acta Crystallographica Section E, 2012)
In the asymmetric unit of the title compound, C16H11FO5S, the 2H-chromene ring is essentially planar, with a maximum deviation of 0.040 (2) Å. The dihedral angle between the 2H-chromene ring and the 4-fluorophenyl ring is 2.17 (8)°. One of the sulfonamide O atoms is approximately coplanar with the benzene ring [C—C—S—O torsion angle = 166.00 (14)°], whereas the other O atom lies well below the plane [C—C—S—O = −61.35 (17)°]. In the crystal, molecules are connected by weak C—H...O hydrogen bonds, forming two-dimensional networks parallel to the ac plane.